Management of Constipation - Toman L Toruan; Ari Fahrial Syam; Marcellus Simadibrata; Murdani Abdullah (The Indonesian Society for Digestive Endoscopy, 2005)
Constipation is the most ignored complaint by doctors and unfortunately, it requires urgent management due to the decreased quality of life. Most cases are functional constipation but there is also a great number of constipation due to organic abnormalities. In an attempt to manage the patient properly, we should put our emphasis on excellent knowledge of pathophysiology of constipation.By using the colonic transit time test, we could determine the type of constipation, which would have an effect on therapy. In most cases, constipation has a good response to high fiber diet and additional laxative medication and surgical therapy is seldom required unless complications have occurred. There is also a suggestion for preventing constipation may be caused by opioid usage. Keywords: Constipation, colonic transit time test, high fiber diet, laxatives